Penilaian Keunggulan Layanan ShopeePay dan DANA Menggunakan Simple Additive Weighting (SAW) - Mhd. Fauzal Pratama; Immanuel Christian Manalu; Anya Nailah Aurellia; Victor Asido Elyakim P (Yayasan Literasi Sains Indonesia, 2024)
Advances in information technology have contributed greatly to the transformation of payment systems, including the emergence of online payment applications or e-wallets. E-wallets such as ShopeePay and DANA have become popular in Indonesia due to the ease, speed, security, and flexibility of transactions they offer. This study aims to evaluate and compare the performance of the two e-wallets using the Simple Additive Weighting (SAW) method. The SAW method is used to analyze and compare alternatives based on a number of predetermined criteria, such as ease of use, security, transaction speed, costs, and user satisfaction levels. Research data was obtained from various sources related to the performance of the two applications, including usage statistics and user reviews. The results of the analysis show that both apps have advantages in certain criteria; for example, ShopeePay is superior in transaction fees, while DANA stands out in speed and security. However, an overall assessment based on the weighting of the criteria reveals a final score that provides important insights for both users and developers. However, analysis using the SAW method provides deeper insight into the advantages of each application based on the weight of the relevant criteria. This study is expected to help users choose an e-wallet that suits their needs and provide guidance for application developers to improve service quality.